2018
DOI: 10.1161/strokeaha.118.021540
|View full text |Cite
|
Sign up to set email alerts
|

Iron Overload Exacerbates the Risk of Hemorrhagic Transformation After tPA (Tissue-Type Plasminogen Activator) Administration in Thromboembolic Stroke Mice

Abstract: Background and Purpose— Recanalization with tPA (tissue-type plasminogen activator) is the only pharmacological therapy available for patients with ischemic stroke. However, the percentage of patients who may receive this therapy is limited by the risk of hemorrhagic transformation (HT)—the main complication of ischemic stroke. Our aim is to establish whether iron overload affects HT risk, to identify mechanisms that could help to select patients and to prevent this devastating complication. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…Accumulating evidence has demonstrated that ferroptosis is dependent on iron or iron-dependent ROS [ 99 , 100 ]. Iron overload causes prolonged upregulation of transport receptors, increases peripheral iron uptake via the BBB, and exacerbates the risk of hemorrhagic transformation [ 101 ]. Besides, iron overload also enhances basal serum lipid peroxidation after early t-PA administration [ 101 ].…”
Section: Ferroptosis In Cirimentioning
confidence: 99%
“…Accumulating evidence has demonstrated that ferroptosis is dependent on iron or iron-dependent ROS [ 99 , 100 ]. Iron overload causes prolonged upregulation of transport receptors, increases peripheral iron uptake via the BBB, and exacerbates the risk of hemorrhagic transformation [ 101 ]. Besides, iron overload also enhances basal serum lipid peroxidation after early t-PA administration [ 101 ].…”
Section: Ferroptosis In Cirimentioning
confidence: 99%
“…Iron overload is a major source of oxidative stress in ischemic brains (Carbonell and Rama, 2007). In addition, iron overload exacerbated the risk of hemorrhagic transformation in animal models of transient ischemia plus early reperfusion (García-Yébenes et al, 2012; García-Yébenes et al, 2018); therefore, in iron-overloaded animals, an initial ischemic event has higher probability to become an ICH. The contribution of iron overload to widespread the damage in the ICH is supported by the fact that systemic iron overload (estimated using high serum FT levels) was associated with higher perihematoma edema and poor outcomes in patients with ICH (Mehdiratta et al, 2008; Perez de la Ossa et al, 2010; Bakhshayesh et al, 2014; Garton et al, 2017).…”
Section: Iron Overload Worsens Neurological Damage Both In Ischemic Smentioning
confidence: 99%
“…In humans, iron, as a necessary microelement, is associated with many diseases, and the exact function of iron in acute ischemic stroke is still debatable. However, a point worth confirming is that iron plays a role in the unfavorable prognosis of acute ischemic stroke and hemorrhage transmission [15,16]. Nevertheless, those studies mainly adopted intravenous medicine treatment, and the actual recanalization was unclear, besides, the research on iron focused mainly on neurological protection and medical treatment after acute ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%